An empirical investigation of socio-economic impacts of agglomeration economies in major cities of Punjab, Pakistan - Naghmana Ghafoor; Sana Fayyaz; Mehrun Nisa; M. Riaz Akbar (Cogent Economics & Finance, 2021)
Agglomeration economies are the external benefits earned from clustering of industries and people in cities. The study assumes unbridled clustering of population in emerging urban agglomerations turning economies into diseconomies. This study empirically investigates the heterogeneous socioeconomic impacts of agglomeration economies in selected cities of Punjab, Pakistan, from 1998 to 2018, using the Pooled Mean Group and the Mean Group techniques of Panel ARDL. Agglomeration economies are determined by population density, number of registered factories, employment size, and housing, in the cities of Punjab. The study designed four indices for socioeconomic conditions using principal component analysis. These include: education-index, healthcare-index, water & sanitation-index, and economic conditions-index. Research findings reveal pressures of high population density, unemployment, and costly housing on educational & healthcare facilities, poor sanitation & waste management, in cities of Punjab, Pakistan. The study suggests that policy makers and urban planners to develop short term and long term policies and development plans for villages and secondary cities to uplift wellbeing of the local population. Nonetheless, cities need to decentralize for sustainable development and management.
Keywords: I15; I25; O18; P36; R1; 330; Agglomeration economies; mean group (MG); pooled mean group (PMG); principal component analysis (PCA); socioeconomic conditions; urban agglomerations